An Update on Molecular Diagnostics for COVID-19 - Islam, Khursheed Ul; Iqbal, Jawed (Frontiers in Cellular and Infection Microbiology, 2020)
A novel strain of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) disease (COVID-19) has been recently identified as an infectious disease affecting the respiratory system of humans. This disease is caused by SARS-CoV-2 that was identified in Chinese patients having severe pneumonia and flu-like symptoms. COVID-19 is a contagious disease that spreads rapidly via droplet particles arising through sneezing and coughing action of an infected person. The reports of asymptomatic carriers changed the scenario of symptom based-diagnosis in COVID-19 and intensified the need for proper diagnosis of the majority of the population to combat the rapid transmission of virus. The diagnosis of positive cases is necessary to ensure prompt care to affected people and also to curb further spread of infection in the population. Collecting samples at the right time and from the exact anatomical site is crucial for proper molecular diagnosis. After the complete genome sequence was available, China formulated RT-PCR as a primary diagnostic procedure for detecting SARS-CoV-2. Many in-house and commercial diagnostic kits have been developed or are under development that have a potential to lower the burden of diagnosis on the primary diagnostic techniques like RT-PCR. Serological based diagnosis is another broad category of testing that can detect different serum antibodies like IgG, IgM, and IgA in an infected patient. PCR-based diagnostic procedures that are commonly used for pathogen detection need sophisticated machines and assistance of a technical expert. Despite their reliable accuracy, they are not cost-effective tests, which a common man can afford, so it becomes imperative to look for other diagnostic approaches, which could be cost effective, rapid, and sensitive with consistent accuracy. To make such diagnostics available to the common man, many techniques can be exploited among, which are Point of Care (POC), also known as bed side testing, which is developing as a portable and promising tool in pathogen diagnosis. Other lateral flow assay (LFA)-based techniques like SHERLOCK, CRISPR-Cas12a (AIOD-CRISPR), and FNCAS9 editor-limited uniform detection assay (FELUDA), etc. have shown promising results in rapid detection of pathogens. Diagnosis holds a critical importance in the pandemic situation when there is no potential drug for the pathogen available in the market. This review sums up the different diagnostic approaches designed or proposed to combat the crisis of widespread diagnosis due to the sudden outbreak of a novel pathogen, SARS-CoV-2 in 2019.